Prototype Pengukur Tinggi Rendah Permukaan & Arus Air Hulu Sungai Lematang Memprediksi Banjir Di Hilir Lematang - Buhori Muslim; Alharia Dinata; Yogi Isro Mukti (Fakultas Ilmu Komputer, Unversitas Muhammadiyah Riau, 2021)
The purpose of this research is to produce a prototype of measuring the flow and height of river water that can help to find out in monitoring the flow and height of river water remotely by using SMS (Short Message Service) on the cellphone. So that it can anticipate before the occurrence of catastrophic floods caused by the height and flow of the river that exceeds the limit. The device used to build a flow meter and river water level with an arduino-based SMS Gateway is a GSM module, Ultrasonic sensor, Water Flow sensor, arduino uno and an arduino IDE application that functions to include programs on arduino The system development method in this research is the RAD method (Rapid) Application Development) and the stages are requirements planning, design workshops and implementation. The way it works on this system is that if the user sends an SMS to the device, the tool will provide information on the strength of the flow and height of the river water using the SMS Gateway facility and the user can find out the information about the current strength and height of the river water via SMS contained on the handphone.